FUNCTIONAL PROPERTIES OF IFNΑ-INDUCED DENDRITIC CELLS IN THE PATIENTS WITH PULMONARY TUBERCULOSIS - L. V. Sakhno (Medicinskaâ Immunologiâ, 2014)
Abstract. Some functional properties of IFNα-induced dendritic cells (DCs) from the patients with pulmonary tuberculosis (PT) were under study. It was revealed that production of IFNγ and IFNα by DCs of the patients was decreased, but TNFα production was preserved at normal level. NO production by DCs from the patients was also reduced. In addition, it has been shown, that DCs of PT patients were characterized by low allostimulatory activity in mixed lymphocyte reaction (MLR), and this defect was more marked in the patients with PPD-anergy. As compared to healthy donors, DCs from the patients with PT (in particular, with PPD-anergy) exhibited a decreased capacity for induction of intracellular expression and production of IFNγ by T-cells. However, DCs from the patients with PPD-anergy were able to stimulate intracellular expression of IL-4 in CD3+T-cell subset. Hence, the results suggest that functional activity of DCs in the patients with PT is altered, and some of these changes are distinctly associated with decreased antigen-specific response. (Med. Immunol., 2008, vol. 10, N 2-3, pp 151-158).